Factors Associated With Enrollment and Adherence in Outpatient Cardiac Rehabilitation in Japan. Issue 3 (May 2015) - Endo, Noriko; Goto, Aya; Suzuki, Tomoko; Matsuda, Shin; Yasumura, Seiji
<x xml:space="preserve">Abstract</x> PURPOSE: Despite the effectiveness of cardiac rehabilitation (CR), the participation percentage is low in Japan. Therefore, we investigated factors associated with enrollment and adherence in outpatient cardiac rehabilitation (OCR) in Japan. METHODS: This was a single-hospital, case-controlled study. During a 2-year study period, 544 patients were hospitalized for ischemic heart disease, heart failure, or open heart surgery, and recommended for in-hospital CR. Among them, 78 OCR participants and 179 randomly selected nonparticipants were included in the study. These 2 groups were compared to examine factors associated with OCR enrollment. In addition, OCR participants were divided into those who continued OCR for 3 months (adherence group) and those who did not (nonadherence group), and these 2 groups were compared to examine factors associated with OCR adherence. Univariate and multivariate logistic regression analyses were conducted for both objectives and included sociodemographic, clinical, and OCR-related variables. RESULTS: OCR enrollment was significantly associated with younger age (OR, 0.96; 95% CI, 0.93–0.98) and shorter distance to the hospital (OR, 0.97; 95% CI, 0.95–0.99). OCR adherence was significantly associated with a history of ischemic heart disease (OR, 6.03; 95% CI, 1.62–22.5) and prescription of antidepressants and/or sleeping pills (OR, 4.14; 95% CI, 1.07–16.0). CONCLUSIONS: The main factors associated with OCR enrollment and adherence were sociodemographic factors related to easier hospital access and clinical conditions that reflected high disease awareness, respectively.